SISTEM PENGUSIR TIKUS BERBUNYI JANGKRIK PADA TANAMAN PADI BERTENAGA SURYA - Indah Martha Fitriani; Allif Cendikiawan; Robbi Kurniawan; Karina Tika Aprilia; Totok Winarno (SENTIA 2016, 2016)
Rice is a plant that produces basic food that is much needed by communities, especially communities in Indonesia. Everyone who plant rice should keep those plants from pests rat so that the rice will be harvested are not damaged. It is not effective because to keep those plants, farmers must be in the rice fields during the day.From above, the problem appeared the idea to create a system of rat repellent. This system is designed to help farmers to keeping the fields from rat attack. The concept of this system that is able to drive out rat that often damaging rice plant in which this system will make sound of crickets that can interfere with hearing rat. This system combined with solar panel as power supply.